2015
DOI: 10.1016/j.cortex.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric association and dissociation of voice and speech information processing in stroke

Abstract: As we listen to someone speaking, we extract both linguistic and non-linguistic information. Knowing how these two sets of information are processed in the brain is fundamental for the general understanding of social communication, speech recognition and therapy of language impairments. We investigated the pattern of performances in phoneme versus gender categorization in left and right hemisphere stroke patients, and found an anatomo-functional dissociation in the right frontal cortex, establishing a new synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…These findings were interpreted as evidence that the right inferior frontal cortex supports the categorization of vocal stimuli into vocal identity categories, with the harder-to-categorize near-boundary stimuli eliciting more activation in right inferior frontal cortex. Consistent with this finding, Jones, Farrall, Belin, and Pernet (2015) observed that stroke patients who had damage to right frontal cortex were impaired in their categorization of talker gender when presented with stimuli from male-female continua; critically, the right STS was intact in these patients, suggesting that these results were not attributable to impairments in early sensory processing. Thus, the right inferior frontal cortex appears to play a critical role in allowing listeners to evaluate voices with respect to known vocal categories, whether these categories are task-relevant (e.g., ones established through training) or socioindexically derived (i.e., categories based on talker-relevant social cues, such as gender or sexual orientation; Johnson, 2008;Munson, 2007).…”
Section: Frontal Lobe Contributions Vocal Identity Processingsupporting
confidence: 58%
See 1 more Smart Citation
“…These findings were interpreted as evidence that the right inferior frontal cortex supports the categorization of vocal stimuli into vocal identity categories, with the harder-to-categorize near-boundary stimuli eliciting more activation in right inferior frontal cortex. Consistent with this finding, Jones, Farrall, Belin, and Pernet (2015) observed that stroke patients who had damage to right frontal cortex were impaired in their categorization of talker gender when presented with stimuli from male-female continua; critically, the right STS was intact in these patients, suggesting that these results were not attributable to impairments in early sensory processing. Thus, the right inferior frontal cortex appears to play a critical role in allowing listeners to evaluate voices with respect to known vocal categories, whether these categories are task-relevant (e.g., ones established through training) or socioindexically derived (i.e., categories based on talker-relevant social cues, such as gender or sexual orientation; Johnson, 2008;Munson, 2007).…”
Section: Frontal Lobe Contributions Vocal Identity Processingsupporting
confidence: 58%
“…In addition to a role for the right temporal lobe, some studies have posited a role for right frontal regions in vocal identity recognition, particularly during tasks that require listeners to categorize voices (Andics, McQueen, & Petersson, 2013;Jones, Farrall, Belin, & Pernet, 2015;Zäske, Awwad Shiekh Hasan, & Belin, 2017) or that require listeners to compare a voice sample to a referent in working memory (Stevens, 2004). Some evidence for the former comes from a study by Andics et al (2013), who presented listeners with a vocal morph continuum where stimuli consisted of two different voices blended in different proportions.…”
Section: Frontal Lobe Contributions Vocal Identity Processingmentioning
confidence: 99%
“…Frontal cortices have previously been found to show activation related to socially salient (e.g. trustworthiness, gender) vocal cues ( Bestelmeyer et al., 2012 ; Charest et al., 2012 ; Jones et al., 2015 ) and to process speaker identity, independently of verbal information ( Latinus et al., 2011 ; Zäske et al., 2017 ). Furthermore, frontal regions such as the inferior frontal gyrus (IFG) are nowadays ascertained to be part of the face perception network ( Duchaine and Yovel, 2015 ); notwithstanding, frontal regions are still considered to have a secondary role in voice perception as demonstrated by the fact that they are not consistently activated during voice-related tasks ( Bonte et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our post hoc analysis, the right IFC ROI shows an intriguing negative correlation to HP, however, only for non-voice sounds. The right IFC may serve a role in salience processing, for example in recognizing salient cues in voice signals ( Johnstone et al, 2006 ; Bestelmeyer et al, 2012 ; Charest et al, 2013 ; Johns et al, 2015 ; Johnson et al, 2021 ). Additionally, this area shares a high functional integration with temporal regions serving voice perception and may assist successful voice recognition ( Aglieri et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%